Teaching and Learning Listening in English as a Foreign Language (EFL) Classroom: A Constructivist Approach - Jayanthi, Muniandy (INTI International University, 2009)
This paper aims to identify th effectiveness of the constructivist approach in teaching, learning and listening among EFL learners, using a sample of international students from INTI International College Penang. Four main purposes of listening: comprehensive, critical, appreciative and therapeutic listening were investigated in relation to the counstructivist approach. In order to identify the efficiency of constructivism in teaching and learning listening in EFL context, various tests, questionnaire and classroom activities have been conducted. The results were compiled and recorded to analyse the significance of constructivist approch in teaching and learning listening skills in EFL classroom. The results were analysed through mean score and standard deviation. The results from the YLLS questionnaire and classroom observation reveal that listening and speaking become their preferred learning style while the pre-test and post-test show that the EFL learners improved well in their listening skills through constructive approach in listening classroom. In conclusion, constructivist learning theory that consists of prior knowledge, social interaction, motivation and construct meaning that relate to real world truly helps the students to progress with their listening skills.